2016
DOI: 10.1037/pag0000103
|View full text |Cite
|
Sign up to set email alerts
|

Early selection versus late correction: Age-related differences in controlling working memory contents.

Abstract: We examined whether a reduced ability to ignore irrelevant information is responsible for the age-related decline of working-memory (WM) functions. By means of event-related brain potentials we will show that filtering is not out of service in older adults but shifted to a later processing stage. Participants performed a visual short-term memory task (change-detection task) in which targets were presented along with distractors. To allow early selection, a cue was presented in advance of each display, indicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 67 publications
6
29
0
Order By: Relevance
“…CDA amplitude was calculated by subtracting ipsilateral from contralateral activity from 350 to 850 ms following the onset of the memory array at three posterior electrodes (P5/P6, PO7/PO8 and CP3/CP4). The time window selected was based on previous studies (Newsome et al, ; Schwarzkopp et al, ). Electrode selection was based on Newsome et al ().…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…CDA amplitude was calculated by subtracting ipsilateral from contralateral activity from 350 to 850 ms following the onset of the memory array at three posterior electrodes (P5/P6, PO7/PO8 and CP3/CP4). The time window selected was based on previous studies (Newsome et al, ; Schwarzkopp et al, ). Electrode selection was based on Newsome et al ().…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have shown that older adults exhibit reduced differentiation of CDA amplitudes across set sizes relative to younger adults, suggesting that the CDA is sensitive to age‐related cognitive changes (Sander, Werkle‐Bergner, & Lindenberger, ; Stormer, Li, Heekeren, & Lindenberger, ). However, other studies have failed to find differences in CDA amplitudes across older and younger age groups (Jost, Bryck, Vogel, & Mayr, ; Schwarzkopp et al, ).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The CDA has become increasingly popular as an index of age-related WM changes (Du, Ji, Chen, Tang, & Han, 2018). However, existing evidence regarding the effects of both age and performance level on CDA amplitudes is equivocal (Jost, Bryck, Vogel, & Mayr, 2011; Sander, Werkle-Bergner, & Lindenberger, 2011; Schwarzkopp, Mayr, & Jost, 2016; Stormer, Li, Heekeren, & Lindenberger, 2013). One possible explanation is that atypical CDA waveforms reflect pathological decline, rather than normal aging.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, detrimental aging effects were found to be most prominent in earlier time intervals of the CDA, which is thought to represent the selection and encoding of visual information (Yamaguchi et al, 1995 ; Gazzaley et al, 2008 ; Jost et al, 2011 ; Störmer et al, 2013 ). Schwarzkopp et al ( 2016 ) explored these age-related differences alongside filtering efficiency (FE), the ability to filter out irrelevant stimuli whilst maintaining the relevant, and suggested that older adults rely on the earlier CDA interval to filter out irrelevant information; whereas, younger adults did so much earlier in time via sensory selection processes. These results indicate that there may be a fundamental dissociation between functional processes and overall performance in working memory as people age.…”
Section: Introductionmentioning
confidence: 99%